Analisis Potensi Sektor Unggulan Diwilayah Provinsi Aceh dengan Menggunakan Metode Location Quotient (LQ) : Studi Kasus : Kota Banda Aceh, Kota Langsa, Kota Lhokseumawe, Kota Sabang dan Kota Subulussalam (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study analyzes the potential of leading sectors in five cities in Aceh Province: Sabang, Banda Aceh, Lhokseumawe, Langsa, and Subulussalam using the Location Quotient (LQ) method. This method is used to identify basic sectors that have comparative advantages and play a role as the main drivers of the regional economy. The data used are secondary data on GRDP by business field from BPS. The results of the study show that each city has different leading sectors according to the characteristics of its region: Sabang excels in the tourism and service sectors; Banda Aceh in the modern service sector such as transportation, finance, and energy; Lhokseumawe in the processing industry and trade; Langsa in the service, trade, and transportation sectors; and Subulussalam in the agricultural and MSME sectors. This study emphasizes the need for the formulation of development policies based on local potential to encourage inclusive and sustainable economic growth in Aceh Province.